1998
DOI: 10.1172/jci2415
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal renal and hepatic glucose metabolism in type 2 diabetes mellitus.

Abstract: Release of glucose by liver and kidney are both increased in diabetic animals. Although the overall release of glucose into the circulation is increased in humans with diabetes, excessive release of glucose by either their liver or kidney has not as yet been demonstrated. The present experiments were therefore undertaken to assess the relative contributions of hepatic and renal glucose release to the excessive glucose release found in type 2 diabetes. Using a combination of isotopic and balance techniques to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
178
1
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(193 citation statements)
references
References 45 publications
9
178
1
5
Order By: Relevance
“…The renal contribution to endogenous glucose production has been a matter of much controversy [4][5][6][7][8][9][10][11][12]28]. Much of the confusion in all likelihood has arisen from the fact that measurements across the renal bed, because of the high renal blood flow of around 1 l/min, are highly susceptible to methodological imprecision as regards analysis of differences in arteriovenous glucose concentrations and dilution of tracers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The renal contribution to endogenous glucose production has been a matter of much controversy [4][5][6][7][8][9][10][11][12]28]. Much of the confusion in all likelihood has arisen from the fact that measurements across the renal bed, because of the high renal blood flow of around 1 l/min, are highly susceptible to methodological imprecision as regards analysis of differences in arteriovenous glucose concentrations and dilution of tracers.…”
Section: Discussionmentioning
confidence: 99%
“…This renewed interest in the metabolic role of the kidney was fuelled by a study by Cersosimo et al [5] who used arteriovenous balance and isotopic dilution techniques to report that in postabsorptive dogs renal glucose utilisation and production each accounted for close to 30% of total glucose turnover in the presence of net balances close to zero. More recent studies in humans have reported that the renal contribution to postabsorptive whole-body glucose production may amount to between 15 and 30%, that glutamine appears to be an important precursor for renal gluconeogenesis and that renal glucose production increases in response to epinephrine and hypoglycaemia and decreases during insulin exposure [6][7][8][9][10][11]. Other investigators, however, have failed to show any significant renal contribution to overall endogenous glucose production [12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore experimental diabetes in animals results in increased renal gluconeogenesis and glucose production in vitro [43,44]. Recently increased renal glucose production has been described in patients with Type 2 diabetes which could contribute to the ensuing hyperglycaemic state [45].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is hypothesized that kidney dysfunction would lead to complex disturbances of glucose appearance in the circulation, resulting in insulin resistance. Metabolic studies in patients with type 2 diabetes mellitus have revealed that renal gluconeogenesissimilarly to hepatic gluconeogenesis-is not suppressed by insulin to a similar extent as in healthy individuals (14). This observation points to the presence of insulin resistance on the level of renal glucose metabolism.…”
mentioning
confidence: 94%